Early rehabilitation and improved outcomes in patients with status epilepticus: Evidence from cases presenting to the emergency department - Hidetaka Onda; Shoji Yokobori (Epilepsia Open)
Abstract Objective Status epilepticus (SE) is a common neurological emergency characterized by prolonged or recurrent seizures that can cause permanent brain damage. Although these seizures can be controlled with appropriate treatment, SE is associated with poor outcomes and a high mortality rate. SE can cause physical, cognitive, and psychological complications at every stage of treatment. Understanding the treatment of SE and its outcomes is important both clinically and socially. Intensive care unit‐acquired weakness and post‐intensive care syndrome are significant issues in survivors of SE. This study aimed to determine if early rehabilitation in the intensive care unit can improve outcomes in patients with SE, given the limited options for intervention after hospitalization. Methods This observational study was approved by our ethics committee (B‐2023‐654) and included 1039 adult patients brought to our center with SE between 2011 and 2023. The patients were divided into a prospectively enrolled rehabilitation intervention group, in which rehabilitation was initiated within 24 h after admission post‐2022, and a retrospective non‐intervention group from before that time. We examined the current status of these patients to determine the value of ultra‐acute rehabilitation and factors associated with favorable outcomes in these patients. The primary outcome was the proportion of patients with a Glasgow Outcome Scale score of 5 at discharge. Results The average age was 52.3 years, with 619 cases aged 65 years or older. Mortality was 2.5%, and 519 patients achieved a Glasgow Outcome Scale score of 5. Rehabilitation initiated within 24 h of hospitalization did not significantly affect the length of hospital stay but did increase home discharge rates and functional independence, particularly in older patients. Significance This study provides a systematic and insightful observational analysis suggesting that early rehabilitation may be associated with improved outcomes in patients with status epilepticus (SE). Further validation and investigation are required. Plain Language Summary When patients experience the severe epileptic condition known as status epilepticus, they are often admitted to the intensive care unit (ICU), where their chances of recovery can be poor. However, this study shows that starting rehabilitation early, even in the ICU, can help improve the recovery of these patients. By beginning rehabilitation soon after admission, patients may have an increased chance of returning home rather than facing long‐term care. This research highlights the potential benefits of early rehabilitation for improving outcomes in patients with severe epilepsy who require emergency care.